Interventions and strategies to improve social support for caregivers of children with chronic diseases: An umbrella review - Yang, Jinrong; Lin, Lin; Gao, Yuqin; Wang, Weiren; Yuan, Lulu (Frontiers in Psychiatry, 2022)
Background Social support is an important approach to improve the psychosocial health status and promote positive coping for caregivers of children with chronic diseases. Such an approach can reduce parenting stress, help resolve parenting difficulties through the use of various social support relationships. Methods We performed an umbrella review methodology using the method of examination, analysis and synthesis of systematic reviews. A PRISMA flow diagram was used to show the search process. The Joanna Briggs Institute was used to appraise the quality of papers and a narrative synthesis was undertaken. Relevant English and Chinese systematic reviews were searched in Embase, PubMed, Web of science, OVID, CNKI, CBM, Wan Fang and Cochrane Library databases, until November 2021, June 2022. Results Out of 1,905 records, we included fourteen systematic reviews for a synthesis. Evidence to promote social support for caregivers of children with chronic diseases was identified from four key aspects: (i) Intervention content; (ii) Intervention forms; (iii) Intervention time; and (iv) Sources of support. Conclusions The findings of this review suggest that a combination of differing interventions, especially for early family, including the content of parenting training or education, attitude building and resource provision, which can implement online is recommend. More interventional studies and quantitative evidence syntheses are still needed. Impact Adequate social support is essential to promote the psychological wellbeing of caregivers of children with chronic diseases. In the early stage of children's diseases, integrating different content and forms of interventions for caregivers' families and actively helping caregivers to identify available support resources can improve social support. The findings from this review can be used to guide caregivers of children with chronic diseases and provide evidence for healthcare professionals and social workers to carry out relevant interventions.